Religious Anthropology: Catalyst for Unravelling Discourses and Fostering Profound Understanding in Arab Society through Islamic Law - Al-Abyadh, Muhtadi; Bustami, Mohammad Reevany; Ikomatussuniah, Ikomatussuniah (Nurani Hukum, 2023)
The Arab-Islamic world remains afflicted by a lack of mutual acceptance, both within Islamic sects and among different religions. This study seeks to alleviate this issue by advocating for the advancement of religious anthropology, aiming to enable researchers to comprehend the religious and social dynamics of both them and others. This understanding is pivotal in promoting values of tolerance and peace, replacing the current undercurrents of violence and animosity. Employing anthropological epistemology, the researcher examines the origins of Arab-Islamic violence through deductive analysis. Notably, the study identifies the jurisprudence “Fiqh” as a one of sources the violence and hostility, in stark contrast to the values of tolerance and peace present in the Holy Qur’an—the primary legislative source. To firmly establish these principles, integrating anthropological studies into both educational and religious sciences curricula is essential. This proactive approach aims to reshape perceptions and foster mutual understanding, thereby guiding the Arab-Islamic world towards unity, empathy, and shared progress.